DEVELOPMENT OF BASIC KUMITE KARATE TRAINING ANDROID BASED ON THE WHITE BELT BLUE KARATE-DO KKI MEDAN IN 2021 - Sinaga, Johanes Nata Nael; Damanik, Saipul Ambri (Journal of Physical Education, Health and Sports Recreation, 2023)
This study aims to produce an android-based application called "Course Karate KKI" which can be used by trainers as a guide and media for basic kumite training that is applied to students.This research is Research and Development research or development research. The development of this media is carried out in several stages, namely gathering information, analyzing information and products to be developed, initial product development, expert validation and first revision, product trials, and final product manufacture. The test subjects were students and trainers of the KKI Wilmar Medan dojo and students and trainers of the KKI Yapim Medan dojo. Which consisted of a small group trial of 7 people and a large group trial of 15 people. The sampling instruments and techniques used to collect data in this research and development are in the form of questionnaires and purposive sampling.The results of this study indicate that the Android-based KKI Karate Course application is suitable for use as a basic kumite karate training guide for trainers and students. This is shown from several assessments that have been carried out by material experts, media experts and field trials. The final results of the assessments from material experts and media experts were declared feasible without any revisions. The results of the small group trial received the "Good" category with a percentage of 90% and the results of the large group trial received the "Good" category with 89%.